Evaluation of Radiation Exposure of Urology Surgeons and Radiology Personnel during Fluoroscopy Guided Surgeries at Shahid Faghihi Hospital in Shiraz - Mohammad Mehdi Movahedi; Alireza Mehdizadeh; Behnam Khalifeh; Samad Amani; Shahram Taeb; Hesamoddin Mostaghimi (Journal of Fasa University of Medical Sciences, 2016)
Background & Objective: Long term exposure to ionizing radiation and its complication have always been concerned by medical physicists. Some previous studies have shown that radiation dose to urology surgeons and involved personnel during mini C-arm fluoroscopy guided surgeries exceeds the secure threshold in some cases. In this study, we intend to evaluate the radiation exposure of urology surgeons and radiology personnel and compare these results to the standard thresholds.